Realiti kemiskinan: Satu kajian teoritikal - Jamil, Norzita; Che Mat, Siti Hadijah (Universiti Kebangsaan Malaysia, 2014)
This article will discuss the methods or methodologies to identify poor households based on the reality of poverty in Malaysia.In Malaysia the context of poverty is explained through a financial perspective or income.Through this concept, poverty is divided into two,absolute poverty and relative poverty.However, poverty in Malaysia is often referred to as absolute poverty income households compared with Poverty Line Income (PLI).This type of measurement, using the income method in identifying an individual or household poor also as a measurement of unidimension. In contrast to the unidimension measurement, measurement of poverty using the multidimensional poverty measure is no longer in use and not as a basic for policy makers to alleviate poverty. The measurement of multidimensional poverty is more on measures and identify “who is poor” based on the shortage experienced by households in each dimension. With this multidimensional poverty measurement, identity or characteristics of the poor exist on two levels or stages.The first stage is the identification of the individual in each dimension and the second involves the definition of poverty through all dimensions.Multidimensional poverty, is a new poverty measurement method that allows us to see a real shortage or reality of poverty experienced by a householder.